Line excitation array detection fluorescence microscopy at 0.8 million frames per second - Chris Martin (Nature Portfolio, 2018)
Demanding biological imaging applications require extremely fast detection methods. Here, the authors demonstrate Line Excitation Array Detection, their developed technique for performing fluorescence microscopy in 3D with 0.8 million frames per second, by applying it to flow cytometry and neuron detection.